Modeling and Simulation of Facts Devices for HVDC Transmission System Voltage Control - Muhd Ikhwan B. Mohd Najib, Muhd Ikhwan (Universiti Teknologi Petronas, 2009)
This report describes about the author Final Year Project (FYP). The title of this FYP is "Modeling and Simulation of FACTS Devices for HVDC Transmission System Voltage Control". The objective of this project is to model any example of HVDC transmission line and apply FACTS devices for the transmission line. By doing that it supposed to give more reliability and flexibility on the performance of the transmission system. As we know, FACTS devices and HVDC are the technology of power electronics which can gives more power control, voltage control and stability control on the conventional power grid. However, as the world is facing large demand for bulk power transmission, more improvements should be made. Therefore this project addresses the improvements for the application of FACTS devices and HVDC.